THE CRUCIFIXION IN THE KORAN The Moslem Point of View - Din, Muhammad (The Muslim world, 1924)
This article gives the very interesting standpoint maintained by a modern Moslem in regard to the crucifixion of Christ. In many respects it is quite a contrast to the orthodox position. The same adverse critical method with which he approaches the New Testament account of Christ's death might work havoc to the Koran if applied with half the vigor. Popular Islam may admit the death of‘Isa, but not the crucifixion as in Baidawi II. p. 21. “It is said, God caused him to die seven hours, and then raised him to heaven.” But Muhammad Din sees that the crux of the matter is the death and resurrection of Christ, and has recourse to the “swoon theory”. To our Christian readers some of the reasons given for not believing in the death of Christ are pathetic, some ingenuous, and others recall the attacks of a half century ago.